2022
DOI: 10.51278/bse.v2i3.427
|View full text |Cite
|
Sign up to set email alerts
|

The Variety of Mathematics Learning Media for Early Childhood in Improving Basic Mathematics Ability

Abstract: Introduction to mathematics in early childhood is a very important cognitive aspect to be given. One of the things that can be done is the development of innovative mathematics learning media for early childhood. This study aims to conduct a literature review related to the various uses of mathematics learning media in early childhood. Data collection was carried out by reviewing all related articles published in the 2019-2022 period. After conducting a thorough review, there were 30 reputable articles from ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Modernization and technological advances today cause many innovations that can be applied in the learning process, one of which is the use of electronic media in learning modules, known as e-modules (Purba et al, 2021); (Rohibni et al, 2022); (Roisatin et al, 2021). Digital learning resources in the form of e-modules can be studied more dynamically using various IT-based devices, as well as obtaining a practical learning experience because the content is following the times and 21stcentury competencies that require students to have critical thinking skills (Anggaira & Sari, 2023), and solve problems (Nuryanto, 2021), creative and innovative (Purba et al, 2021), collaborative and communicative (Sutama et al, 2021;Fajar, A., et al, 2022).…”
Section: A Introductionmentioning
confidence: 99%
“…Modernization and technological advances today cause many innovations that can be applied in the learning process, one of which is the use of electronic media in learning modules, known as e-modules (Purba et al, 2021); (Rohibni et al, 2022); (Roisatin et al, 2021). Digital learning resources in the form of e-modules can be studied more dynamically using various IT-based devices, as well as obtaining a practical learning experience because the content is following the times and 21stcentury competencies that require students to have critical thinking skills (Anggaira & Sari, 2023), and solve problems (Nuryanto, 2021), creative and innovative (Purba et al, 2021), collaborative and communicative (Sutama et al, 2021;Fajar, A., et al, 2022).…”
Section: A Introductionmentioning
confidence: 99%
“…There are many researchers found that the kinds of of application learning media can engage the students learning and influence the the effective learning program, hence it can give impact of students interest in learning process. (Purba, et al, 2021;Rohibni, et al, 2022;Wijaya, A., & Salis, R. N. 2022;Laili, et al, 2022). Hence the suitable of application learning media is essential for beginning of learning process (Pramesti, M., & Amelia, W. 2022.…”
Section: Introductionmentioning
confidence: 99%